Turtle excluder device (TED) in trawl nets: applicability in Indian trawl fishery - Rao, G Sudhakara (Indian Journal of Fisheries, 2012)
Turtle fishing was banned in India from 1977 as turtles were declared as protected animals under Schedule I of the IndianWildlife (protection) Act 1972 as per the amendments made to the schedule in September 1977. Similar restrictions wereobserved in many other countries. In spite of these restrictions, there is illegal fishing for turtles in some countries. Apartfrom these illegal activities, there is considerable amount of incidental mortality of turtles due to fishing activities liketrawling and gill netting. India, Australia and the USA are the major contributors to the mortality of turtles due to fishingactivities, particularly the prawn fishing operations. In 1980, a unique separator trawl design called the Turtle ExcluderDevice (TED) was developed by the National Marine Fisheries Service (NMFS) of USA to reduce the incidental capture ofendangered sea turtles by shrimp trawls. The NMFS developed a number of TED designs to improve their functioning. From1993 shrimp season onwards, USA implemented revised federal TED regulations which are more effective in reducing turtlemortality. India also started testing different types of imported TEDs in view of the US embargo on imports from countriesnot implementing TEDs. Central Institute of Fisheries Technology (CIFT), Fishery Survey of India (FSI) and Central Instituteof Fisheries Navigation and Engineering Training (CIFNET) conducted experiments with imported TEDs. These experimentscould not impress the fishermen as there are no comparable data from the traditional trawl nets and trawl nets with TEDssimultaneously. Field trials of the CIFT-TED have been carried out off Cochin, Visakhapatnam and Paradeep. CIFT-TED isnow being popularized in maritime states in collaboration with MPEDA and respective state fisheries departments. In spiteof all the assurances of the government agencies in India, the USA, Australia and other shrimp trawling countries, fishermenstill feel that there is considerable escapement of shrimp with TEDs attached trawl nets which is the major bottleneckaffecting implementation of TEDs in India and elsewhere.